Pergeseran Otoritas Keagamaan di Ruang Publik Virtual X (Twitter) - Muttaqin, Husnul (The Sociology of Islam, 2024)
The social media platform X (Twitter) has evolved into a virtual public space extensively utilized by its users to discuss various issues, including religion. This phenomenon presents an intriguing subject for investigation, particularly concerning the resurgence of traditional religious authority into the virtual public sphere and the influential capacity of social media algorithms to direct and shape users' religious perspectives. This research examines the shift in religious authority within the virtual public space of social media platform X (Twitter). Qualitative research methods will be employed in this inquiry. The study utilizes data crawling techniques facilitated by an application built using the Python programming language to define the research scope. The study yields several noteworthy findings. Firstly, the emergence of traditional religious authority appears to facilitate the proliferation of more open and substantive religious discussions within the virtual public space. Secondly, the emergence of two novel types of authority within the virtual public space, namely anonymous human authority and impersonal non-human authority. Anonymous human authority derives its legitimacy from social media reputation, while impersonal non-human authority manifests in the form of social media algorithms capable of influencing and shaping religious perspectives through the mechanism of creating algorithmic circles.